Kapü kameakuē: o que colhi com Inute Tuta e os Kwazá-Aikanã - Sucupira, Gicele (Universidade Federal de São Carlos, 2024)
This thesis is an anthropological exercise based on my learning from the indigenous sage Inute Tuta and the Kwazá-Aikanã people from the Dois Irmãos village in the Kwazá’s Rio São Pedro Indigenous Land, located in the southern part of the state of Rondônia. With Inute Tuta, I sought to 'gather' what the Kwazá-Aikanã wish to record for non-indigenous people and for future generations. The mukudu (body ornaments), indigenous names, photographs, soccer, and açaí are important means of relating to others and showcasing who the Kwazá-Aikanã are. From the mukudu, central theme of Inute Tuta's work, I learned about 'utilization,' a Kwazá-Aikanã way of living that expresses itself in an ethics of life, with rules and guidelines for relationships with others, in which one cares for, values, respects, and uses only what is necessary of what is available. This way of living is essential for survival in a world where the assaré (non-Indians) are the majority and scarcity is increasingly present.This is the first ethnography about the Kwazá-Aikanã following the guidance of the people themselves, particularly that of Inute Tuta.
59 / 5.000 Kapü kameakuē: what I learned from Inute Tuta and the Kwazá-Aikanã
Keywords: Kwazá-Aikanã; Rondônia; Educação; Artesanato; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA